RONC-14. Olfactory Perception During Proton Radiation and Differences in Frequency of Olfactory Perceptions Based on Proton Craniospinal Irradiation Technique for Pediatric Brain Tumor Patients. (3rd June 2022) - Ioakeim-Ioannidou, Myrsini; Erfani, Parsa; Urell, Tobias; Daartz, Juliane; Berv, Julia; Leahy, Shannon; Fullerton, Barbara; Bolton, Rachel; Yock, Torunn; Tarbell, Nancy; Yeap, Beow; MacDonald, Shannon
Abstract: BACKGROUND: Unusual olfactory perception has been reported during brain radiation treatments but is infrequent and does not typically interfere with the ability to deliver treatment or cause notable distress. Methods: We performed a retrospective review of 127 pediatric patients treated with proton radiation therapy (PRT) for primary brain tumors in a single institution between 2016-2021. Patients received PRT to the brain as part of craniospinal irradiation (CSI) followed by a boost to the brain. Proton CSI was delivered with 3D-CRT protons (n=53) or pencil beam scanning technique (PBS) (n=74). Within the PBS group, treatment delivery to the CSI utilized a single PA field (n=24) or two posterior oblique fields (n=50). We collected data on abnormal olfactory sensations, nausea/vomiting, and the use of medical intervention for those symptoms. Results: Our cohort included 80 males and 47 females. The median age of patients was 10 years old (range, 3 – 21). Seventy-one patients received concurrent chemotherapy. Prior to PRT, 31 patients were nauseous. During the radiation course, 104 patients developed worsening nausea while 63 patients reported emesis. Four patients vomited while receiving radiation. Seventeen patients reported olfactory perceptions during CSI. We found a higher rate of olfactory perception in patients treated with PBS (n=16, 22%) than 3D-CRT (n=1, 2%) (p=0.001) and, within the PBS group, patients treated with a single PA field (n=11, 46%) than two oblique fields (n=5, 10%) (p=0.002). Seventy-eight patients required intervention including addition of anti-emetic or anti-anxiety medication. Two patients required sedation due to the malodorous smell during CSI. We did not find any significant difference in nausea/vomiting based on treatment technique. Conclusions: PBS and PBS technique influence olfactory perceptions but not the occurrence of the rate of nausea/vomiting. Further studies should be performed to validate these findings and determine techniques to minimize unpleasant olfactory perceptions.